2020
DOI: 10.1186/s13613-020-00744-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical mask on top of high-flow nasal cannula improves oxygenation in critically ill COVID-19 patients with hypoxemic respiratory failure

Abstract: Objective Critically ill patients admitted in ICU because of COVID-19 infection display severe hypoxemic respiratory failure. The Surviving Sepsis Campaign recommends oxygenation through high-flow nasal cannula over non-invasive ventilation. The primary outcome of our study was to evaluate the effect of the addition of a surgical mask on a high-flow nasal cannula system on oxygenation parameters in hypoxemic COVID-19 patients admitted in ICU who do not require urgent intubation. The secondary outcomes were rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 20 publications
5
43
0
Order By: Relevance
“…In a prospective study, Montiel et al suggested that a surgical mask placed on patient’s face treated with HFNO improves oxygenation [ 22 ]. Our study was not designed to evaluate this effect or a potential association with a lower risk of IMV.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Montiel et al suggested that a surgical mask placed on patient’s face treated with HFNO improves oxygenation [ 22 ]. Our study was not designed to evaluate this effect or a potential association with a lower risk of IMV.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be explained by a decrease in room air entrainment diluting the gas mixture. 5 In contrast, Binks and colleagues 6 reported that F I O 2 , which was examined using a carbon dioxide sample line attached to a 16 G cannula, did not differ according to the position of the surgical mask relative to a Hudson oxygen mask at a flow rate of 6 L min −1 . However, the figure in their report showed significantly higher expiratory oxygen concentration when wearing an oxygen J o u r n a l P r e -p r o o f…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%
“… 32 Early start: If PaO2:FiO2 < 300 or SpO2 < 93% on O2 > 5 L/min or SpO2 < 94% with FiO2 40% 33 Late start: SpO2 < 92% under O2 at 15 L/min and or PaFiO2 < 150 23 Start with: Ramp up from 30 L/min until 60 L/min to accustom the patient (40–50 if not tolerated); FiO2 to maintain spO2 > 93%; Temperature 31−37º according to patient’s comfort A surgical mask should be placed over the nose and mouth of a patient with a properly fitted nasal cannula before initiating therapy. It not only reduces droplet deposition 34 but also improves COVID-19 patient’s oxygenation 35 without any clinically relevant side effect, except for a moderate reduction in CO2 clearance. 34 This may require increasing flow rate of HFNC if the patient is displaying increased work of breathing.…”
Section: Criteria To Start Hfncmentioning
confidence: 99%
“…A surgical mask should be placed over the nose and mouth of a patient with a properly fitted nasal cannula before initiating therapy. It not only reduces droplet deposition 34 but also improves COVID-19 patient’s oxygenation 35 without any clinically relevant side effect, except for a moderate reduction in CO2 clearance. 34 This may require increasing flow rate of HFNC if the patient is displaying increased work of breathing.…”
Section: Criteria To Start Hfncmentioning
confidence: 99%